(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article deals with intercultural aspects of metaphorical modeling of political reality in Kazakh, Russian, Bulgarian and American presidential discourse. The texts of Presidents’ Addressees for 2021-2022 were used as the research material. The methodological basis is the concept of metaphor as a cognitively modeled phenomenon that plays an essential role in representing the linguistic view of the world. The subject of the research is the general and specific peculiarities and regularities of representation of reality through the use of metaphors and metaphor models in the Addressees of Heads of States. There are implemented cognitive-discursive and contextual analysis methods, modeling, and the linguostatistical method. We suppose that the construction of metaphor models, calculation of frequency of use of linguistic means and the statistical data analysis allows us to show the society’s value priorities and the country’s political reality. Moreover, it will help to reveal specifics of the people’s thinking and the peculiarities of their way of life at a particular historical period. The comparative analysis showed that in the texts of the Addressees for studied years, the dominant metaphorical model used in the speeches of the presidents of the four countries is a military metaphor, and the rest are associated with man, nature, landscape, mechanism, theater, sports, etc. This work represents a separate stage of studying metaphor in political discourse. It implies exploring other aspects of the problem and expanding the research material.